How did Location Affect Adoption of the Commercial Internet? Global Village, Urban Density and Industry Composition - Chris Forman; Avi Goldfarb; Shane M Greenstein (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
The authors test opposing theories on how urban locations influenced the diffusion of Internet technology. They find evidence that, controlling for industry, participation in the Internet is more likely in rural areas than in urban areas. Nevertheless, talk of the dissolution of cities is premature. Frontier Internet technologies appear more often at establishments in urban areas, even with industry controls. Major urban areas also contain many establishments from information technology-intensive industries, whose presence could reinforce the concentration of frontier Internet technologies in these areas. However, information technology-intensive industries are numerous and widespread. Hence, so is the use of frontier technology.
Keywords: R0; L86; L63; 330; Räumliche Innovationsdiffusion; Internet; Stadt; Ballungsraum; USA